Supramolecular synthons in bumetanide cocrystals and ternary products - Allu, Suryanarayana; Bolla, Geetha; Tothadi, Srinu; Nangia, Ashwini (Crystal Growth & Design, 2017)
A novel design strategy for cocrystals of the diuretic sulfonamide drug bumetanide (BUM) with carboxamides is reported based on reliable supramolecular synthons. Binary cocrystals of BUM with pyridine carboxamides, pyridones, and cytosine were obtained by solvent assisted grinding followed by solution crystallization. All cocrystal structures exhibit hydrogen bonding of the coformer with the carboxylic acid group of BUM via heterosynthons which replace the acid homodimer in the drug crystal structure. Pyridones are inserted as N-H center dot center dot center dot O dimers which are in turn bonded to the acid group of BUM, while the pyridine amide coformers interact via the acid amide heterosynthon. Cocrystal polymorphs were obtained for bumetanide isonicotinamide cocrystal structure with the sulfonamide pyridine and sulfonamide acid synthons. Careful crystal packing analysis of BUM structure and nine new binary adducts gave an idea for the design ternary cocrystals, and subsequently four new ternary crystalline products were crystallized. Whereas the binary cocrystal structures were confirmed by single crystal diffraction, the ternary combinations were chatacterized by their unique powder X-ray diffraction patterns as well as by thermal and spectroscopic techniques.